Relationship between prop (6-n-propylthiouracil) taster status and preference for different taste food groups among university students - Syathirah Hanim A.H.,; Ruhaya H.,; Norkhafizah S.,; Marina A.M., (Penerbit Universiti Kebangsaan Malaysia, 2020)
It is reported by many studies that supertasters are highly sensitive towards strong taste such as bitter, and therefore had a lower preference for those foods. However, whether the findings apply to all cultures is still debated. The study on the Malaysian population regarding their PROP status is scarce. Thus, we carried out a study to determine whether 6-n-propylthiouracil (PROP) sensitivity status affects the food preference among university students in Kelantan, Malaysia. PROP taster status was determined using PROP test paper and food preference was determined using a questionnaire. The results indicated that there was no significant difference (p>0.05) in the food preference between supertasters, medium tasters, and non-tasters except for jelly, dark chocolate, and plain tea. Contrary to popular belief that PROP taster status was negatively associated with a bitter taste, the present study found a positive correlation between PROP scores and few foods from the bitter food group (bitter gourd, dark chocolate, and plain tea) and also sweet food group (chocolate cake and chocolate spread). This indicates that the genetic factor that is associated with PROP sensitivity does not play important role in determining the food preference among Malaysians. Instead, other factors such as culture and environment could be more influential in defining the way Malaysians select their foods.